Agricultural activities during July - Kumar, Dinesh; Sepat, Seema (Indian Farming, 2019)
In general, the south-west monsoon covers the whole country in the month of July. Farmers must take advantage of the rainy season in sowing/planting the crops, conserving valuable water in the soil, ponds and other structure for future use. As far as possible, the water of rain should not be allowed out of the fields and especially in the rainy conditions, it should be stored in the soil. Also, water logging in some areas may cause damage to certain crops, e.g. arhar, urad, mung, soybean, groundnut, maize, sorghum and pearl millet, etc. Hence, draining off excess water from such lands may be given priority. The transplanting of rice would continue during this month also. Sowing of crops, like, jowar, bajra, maize, urad, moong and fodder crops can be accomplished in this month. Apart from the above activities, many types of cultural operations in vegetables, flowers and some fruit trees are also accomplished in this month. Therefore, in the present article, the major agricultural activities during July are discussed.